Effectiveness of zoom-based online sessions in developing research skills among geographically distant participants: a cross-sectional study - Masood Jawaid; Zainab Aqeel Khan; Zubia Masood; Rehan Ahmed Khan (Khyber Medical University Journal)
Objective: To evaluate the effectiveness of Zoom-based online meetings in enhancing research skills among geographically distant participants. Methods: This descriptive cross-sectional study analyzed data from the “Certification in Clinical Research (CCR)” course, conducted from November 2023 to May 2024 in Karachi, Pakistan. Ethical approval was obtained from Ameen Medical and Dental Center (Ref# ERC-CIRS-2023-656). The course included five bi-weekly online sessions on various aspects of clinical research, delivered via Zoom. A total of 177 participants from diverse medical fields attended, using personal computers for synchronous learning. Each 120-minute session featured presentations, interactive discussions, and a Q&A segment. Participants provided feedback through a structured questionnaire assessing presenter quality, content, technology, and information on a 5-point Likert scale. Data were analyzed using SPSS version 26. Results: Of the 177 participants, 20% were new to online learning. Overall feedback was positive, with mean ratings of 4.5 for presenters, 4.3 for content, 4.0 for information, and 4.3 for technology. Presenters in session 1 received the highest rating (4.7 ± 0.5), while technology in session 2 had the lowest (3.4 ± 1.2). Around 60% of participants revisited recorded sessions, with the highest watch time reaching 340.5 ± 25.5 minutes. Participants actively engaged, with an average of 675.3 ± 22.4 chat posts per session. Conclusion: Zoom-based online meetings were highly rated by participants, fostering collaborative learning through active engagement and facilitator interactions despite minor technical challenges. Session recordings benefited both absent participants and content review. Further research is required to assess long-term skill retention.